Sago Palm: Multiple Contributions to Food Security and Sustainable Livelihoods - Ehara, Hiroshi; Toyoda, Yukio; Johnson, Dennis V. (Springer Nature, 2018)
Under-utilized food resource; Metroxylon sagu; Starch production; Sago palm forest; Sago sugar